Drifting marine plastics as new ecological habitats for harmful eukaryotic microbial communities in Jeju Strait, Korea - Lee, Bora; Park, Myung Gil (Frontiers in Marine Science, 2022)
Micro/macro plastics are ubiquitous and are emerging agents causing many ecological problems in marine environments. Plastics carry various fouling organisms, including harmful microorganisms, that could potentially have ecological impacts on the marine environment and eventually human health. In this study, marine micro/macro plastics drifting at multiple locations in the Jeju Strait and around Jeju Island, Korea, were collected and analyzed. DNA metabarcoding and scanning electron microscopy were used to characterize the species composition of the attached eukaryotic microbial communities, with a special emphasis on harmful or toxic dinoflagellates, fungi, and parasites. A total of 1,035 eukaryotic microbial operational taxonomic units (OTUs) were identified from plastics and surrounding seawater samples. Two types of samples shared half of the eukaryotic OTUs, and of which approximately 12% were unique to plastic samples. These included 68 Archaeplastida (54.0%), 45 Stramenopiles (35.7%), 12 Opisthokonta (9.5%), and 3 Alveolata (2.4%) OTUs. The harmful or toxic dinoflagellates observed on the plastic surface were Alexandrium, Coolia, Dinophysis, Heterocapsa, Karlodinium, Noctiluca, Ostreopsis, Prorocentrum, Scrippsiella, and Tripos. The most dominant parasite community of the plastisphere, was represented by fungi (42% of all parasite OTUs), followed by Oomycota (33%), Stramenopiles (14%), and dinoflagellates (12%). Nonetheless, this study demonstrates that the eukaryotic communities are considerably shared between the plastisphere and seawater. This implies that plastics serve as a new ecological habitat in the sea, and could function as dispersal vectors that facilitate the spread of harmful eukaryotic species and parasites.